Socioeconomic Determinants of Health Status; Evidence from Nusa Tenggara Barat – Indonesia - Delfia Tanjung Sari; Muhammad Dani Susetiawan (Fakultas Ekonomi Universitas Andalas, 2025)
Health is a vital component of human capital, influencing long-term economic productivity and social well-being. In developing regions such as Nusa Tenggara Barat (NTB), Indonesia - where poverty, limited education, and underdeveloped health infrastructure persist - understanding the socioeconomic drivers of health is crucial for inclusive development. This study examines the impact of socioeconomic and demographic factors on indivual health status using data from the 2019 National Socioeconomic Survey (SUSENAS) and a logistic regression approach. The results show that individuals with higher education, stable employment, greater household expenditure, and health insurance coverage are significantly more likely to have good health. Conversely, older individuals and women are less likely to do so. The study finds that income, residential location, education, age, marital status, and gender significantly affect health outcomes in NTB, while employment status does not. Higher income and urban residence improve health, but unexpectedly, higher education is linked to poorer short-term health, likely due to reporting bias, stress, or lifestyle factors. These results support human capital theory while revealing context-specific dynamics, underscoring the need for targeted poverty reduction, rural healthcare expansion, gender-sensitive interventions, and comprehensive health promotion across all education levels. Abstract Kesehatan merupakan komponen penting dari modal manusia, yang memengaruhi produktivitas ekonomi jangka panjang dan kesejahteraan sosial. Di wilayah berkembang seperti Nusa Tenggara Barat (NTB), Indonesia - di mana kemiskinan, pendidikan yang terbatas, dan infrastruktur kesehatan yang belum berkembang masih menjadi masalah - memahami faktor-faktor sosioekonomi yang memengaruhi kesehatan sangat penting untuk pembangunan inklusif. Studi ini menganalisis dampak faktor-faktor sosioekonomi dan demografis terhadap kesehatan yang dilaporkan sendiri menggunakan data dari Survei Sosioekonomi Nasional (SUSENAS) 2019 dan pendekatan regresi logistik. Hasil menunjukkan bahwa individu dengan pendidikan lebih tinggi, pekerjaan stabil, pengeluaran rumah tangga lebih besar, dan memiliki jaminan Kesehatan cenderung lebih sehat. Sebaliknya, individu yang lebih tua dan perempuan cenderung kurang sehat. Studi ini menemukan bahwa pendapatan, lokasi tempat tinggal, pendidikan, usia, status perkawinan, dan jenis kelamin secara signifikan mempengaruhi kesehatan di NTB, sementara status pekerjaan tidak. Pendapatan yang lebih tinggi dan tempat tinggal di perkotaan meningkatkan kesehatan, tetapi secara tak terduga, pendidikan yang lebih tinggi terkait dengan kesehatan yang lebih buruk, kemungkinan disebabkan oleh bias pelaporan, stres, atau faktor gaya hidup. Hasil ini mendukung teori modal manusia sambil mengungkap dinamika spesifik konteks, menyoroti kebutuhan akan pengurangan kemiskinan yang ditargetkan, perluasan layanan kesehatan di pedesaan, intervensi yang sensitif terhadap gender, dan promosi kesehatan komprehensif di semua tingkat pendidikan.